Enterprise Architecture Design in XYZ Kindergarten School Using the TOGAF ADM Framework for the Digital Transformation of Children's Education - Ratna Lindawati; abdul latif; Trifebi Shina Sabrila; M. Ulil Albab (LPPM Universitas Sari Mulia, 2025)
Operational management at XYZ Kindergarten School is currently still dominated by manual processes, starting from recording attendance to reporting student development. This triggers the risk of inefficiency and loss of historical data on child development. This research aims to design a comprehensive enterprise architecture (EA) for XYZ Kindergarten School using the TOGAF ADM (Architecture Development Method) methodology. The main focus of the research is to align preschool education business processes with integrated information technology solutions. The results of the study formulated the blueprint of the Kindergarten School Information System (SISTK) which includes multimedia-based digital portfolio management and two-way communication systems. The implementation of this design is projected to optimize teacher performance and provide transparency of development data for parents in real-time.